Composite Colloidal Gels Made of Bisphosphonate‐Functionalized Gelatin and Bioactive Glass Particles for Regeneration of Osteoporotic Bone Defects - Diba, Mani; Camargo, Winston A.; Brindisi, Mariateresa; Farbod, Kambiz; Klymov, Alexey; Schmidt, Stephan; Harrington, Matthew J.; Draghi, Lorenza; Boccaccini, Aldo R.; Jansen, John A.; van den Beucken, Jeroen J. J. P.; Leeuwenburgh, Sander C. G. (Advanced functional materials, 2017)
Injectable composite colloidal gels are developed for regeneration of osteoporotic bone defects through a bottom‐up assembly from bisphosphonate‐functionalized gelatin and bioactive glass particles. Upon bisphosphonate functionalization, gelatin nanoparticles show superior adhesion toward bioactive glass particles, resulting in elastic composite gels. By tuning their composition, these composite colloidal gels combine mechanical robustness with self‐healing ability. The composite colloidal gels support cell proliferation and differentiation in vitro without requiring any osteogenic supplement. In vivo evaluation of the composite colloidal gels reveals their capacity to support the regeneration of osteoporotic bone defects. Furthermore, the bisphosphonate modification of gelatin induces a therapeutic effect on the peri‐implantation region by enhancing the bone density of the osteoporotic bone tissue. Consequently, these composite colloidal gels offer new therapeutic opportunities for treatment of osteoporotic bone defects. Injectable composite colloidal gels are developed via bottom‐up assembly from bisphosphonate‐functionalized gelatin and bioactive glass particles. These composite gels combine mechanical robustness with self‐healing ability, and stimulate cellular activities in vitro. Moreover, these materials exhibit a strong capacity to support the regeneration of osteoporotic bone defects, and also induce a therapeutic effect on peridefect osteoporotic bone in vivo.